From semantics to feelings: how do individuals with schizophrenia rate the emotional valence of words? - Pinheiro, Ana (2012)
Schizophrenia is characterized by both emotional and language abnormalities. However, in spite of reports of preserved evaluation of valence of affective stimuli, such as pictures, it is less clear how individuals with schizophrenia assess verbal material with emotional valence, for example, the overall unpleasantness/displeasure relative to pleasantness/attraction of a word. This study aimed to investigate how schizophrenic individuals rate the emotional valence of adjectives, when compared with a group of healthy controls. One hundred and eighty-four adjectives differing in valence were presented. These adjectives were previously categorized as “neutral,” “positive” (pleasant), or “negative” (unpleasant) by five judges not participating in the current experiment. Adjectives from the three categories were matched on word length, frequency, and familiarity. Sixteen individuals with schizophrenia diagnosis and seventeen healthy controls were asked to rate the valence of each word, by using a computerized version of the Self-Assessment Manikin (Bradley and Lang, 1994). Results demonstrated similar ratings of emotional valence of words, suggesting a similar representation of affective knowledge in schizophrenia, at least in terms of the valence dimension.